USAGE OF CREATIVE TECHNOLOGIES IN TEACHING ENGLISH LANGUAGE IN THE INTERCULTURAL COMMUNICATION PROCESS - Ябурова, Олена (Професіоналізм педагога: теоретичні й методичні аспекти, 2018)
The article under consideration is devoted to studying the effectiveness of intercultural communication of Ukrainian students at higher educational establishments. The question of using social and pedagogical, methodological and linguistic means in the process of intercultural communication is observed through studying a foreign language. The author stresses that the content of intercultural communication is based on raising students’ positive attitude to the country whose linguistic culture is studied, a high level of studying informative process value, providing conditions for authentic communication at the intercultural level, assessing and analyzing events which give an opportunity for a future specialist to be integrated in the open intercultural space. The aim of the article is to analyze theoretical and methodological preconditions of using creative technologies while studying English in the process of intercultural communication in a specific way. The author also focuses on defining and describing the main constituent parts of the strategies how to implement intercultural communication through studying languages. Taking the results of the done theoretical analysis into account, the author recommends the set of special linguistic exercises, designed according to the main creative approaches to studying a foreign language in the process of intercultural communication.